Case Report: Chronic Adaptive Deep Brain Stimulation Personalizing Therapy Based on Parkinsonian State - Nakajima, Asuka; Shimo, Yasushi; Fuse, Atsuhito; Tokugawa, Joji; Hishii, Makoto; Iwamuro, Hirokazu; Umemura, Atsushi; Hattori, Nobutaka (Frontiers in Human Neuroscience, 2021)
We describe the case of a 51-year-old man with Parkinson’s disease (PD) presenting with motor fluctuations, who received bilateral subthalamic deep brain stimulation (DBS) with an adaptive DBS (aDBS) device, Percept™ PC (Medtronic, Inc., Minneapolis, MN). This device can deliver electrical stimulations based on fluctuations of neural oscillations of the local field potential (LFP) at the target structure. We observed that the LFP fluctuations were less evident inside the hospital than outside, while the stimulation successfully adapted to beta oscillation fluctuations during the aDBS phase without any stimulation-induced side effects. Thus, this new device facilitates condition-dependent stimulation; this new stimulation method is feasible and provides new insights into the pathophysiological mechanisms of PD.